La Philosophie Politique de Hegel comme Épistémologie - Kervégan, Jean-François (Revista Eletrônica Estudos Hegelianos, 2021)
In the following text, I propose an unusual interpretation of the famous maxim of the Preface to the Principles of the Philosophy of Right: “Was vernünftig ist, das ist wirklich; und was wirklich ist, das ist vernünftig”. I understand it not as a politically conservative normative judgment (this is the usual interpretation), but as an epistemological judgment concerning the way in which philosophical discourse is related to reality. My intention is to take seriously Hegel’s thesis according to which the aim of philosophy is not to prescribe to the world what it should be, but rather to define the way in which it should be known.